2023
DOI: 10.3389/fnins.2023.1215097
|View full text |Cite
|
Sign up to set email alerts
|

Retinal electrophysiology in central nervous system disorders. A review of human and mouse studies

Abstract: The retina and brain share similar neurochemistry and neurodevelopmental origins, with the retina, often viewed as a “window to the brain.” With retinal measures of structure and function becoming easier to obtain in clinical populations there is a growing interest in using retinal findings as potential biomarkers for disorders affecting the central nervous system. Functional retinal biomarkers, such as the electroretinogram, show promise in neurological disorders, despite having limitations imposed by the exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 315 publications
0
5
0
Order By: Relevance
“…To identify the optimal time interval in which to examine group differences, the region where there is greatest separation of the confidence interval boundaries could be used to localize the most suitable time or registered time point or interval. Thus, this report introduces the potential analysis of the ERG waveform using elements of FDA theory as an additional tool with which to analyze the ERG in retinal and neurological disorders [ 17 , 46 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify the optimal time interval in which to examine group differences, the region where there is greatest separation of the confidence interval boundaries could be used to localize the most suitable time or registered time point or interval. Thus, this report introduces the potential analysis of the ERG waveform using elements of FDA theory as an additional tool with which to analyze the ERG in retinal and neurological disorders [ 17 , 46 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…FDA has been implemented to aid diagnosis in cardiology using electrocardiogram signals [ 49 ], gait patterns in Parkinson’s disease [ 50 ] and electroencephalograph recordings to assess driver fatigue [ 51 ]. Here our focus is on the ERG, and this method may therefore assist in expanding the application of the ERG to not only retinal [ 46 ] but also in the classification neurological disorders where multiple genetic and environmental factors may interact to hinder the identification of distinct phenotypical entities based on conventional ERG measures [ 38 , 48 , 49 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing the ERG waveform, potential biomarkers can be identified for the early detection of ADHD and bipolar disorder. Researchers have applied signal analysis techniques, such as wavelets and variable frequency complex demodulation, to studies in ASD [3] and ADHD [46] to fully leverage the potential of ERG in classifying or detecting CNS disorders at an earlier stage. These initial studies have identified the potential for identifying features extracted from signal analysis to improve ML classification models.…”
Section: Discussionmentioning
confidence: 99%
“…The ERG is a non-invasive ophthalmological examination method of the retina, which is increasingly applied in the field of neuropsychiatric research [10][11][12][13]. Given its embryological origin as part of the central nervous system [14], the retina is often regarded as an easily accessible "window to the brain" [15].…”
Section: Introductionmentioning
confidence: 99%